Dynamics of a Market Share Model for Enterprises with Coopetition Strategy - Mingxia Zhao (Discrete Dynamics in Nature and Society)
A deterministic model is used to study the change of the market share with coopetition strategy for enterprises. The model takes into consideration both coopetition enterprises and other enterprises, and the coopetition threshold R0 is identified and global dynamics are completely determined by R0. It shows that R0 is a global threshold parameter in the sense that if R0<1, the coopetition free equilibrium is globally stable and the market share of coopetition enterprises tends to zero, whereas if R0>1, there is a unique coopetition equilibrium which is globally attractive with some conditions, and thus the market share of coopetition enterprises tends to a steady state value. By some sensitivity analysis of R0 on parameters, we conclude that the size of the coopetition threshold R0 and coopetition equilibrium depended on the cooperation competitiveness of coopetition enterprises.